2019
DOI: 10.1016/j.bbadis.2018.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational modifications of Parkinson's disease-related proteins: Phosphorylation, SUMOylation and Ubiquitination

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder characterized by loss of dopaminergic neurons in the nigrostriatal pathway. The etiology of PD remains unclear and most cases are sporadic, however genetic mutations in more than 20 proteins have been shown to cause inherited forms of PD. Many of these proteins are linked to mitochondrial function, defects in which are a central characteristic of PD. Post-translational modifications (PTMs) allow rapid and reversible control over protein function. Largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…“Cellular protein modification,” “Nucleic acid binding transcription factor activity,” “Cell death,” “Catabolic process,” were overrepresented among the biological processes affected. Cellular protein modifications such as phosphorylation, ubiquitination, truncation, acetylation, nitration, and sumoylation of PD‐linked proteins have emerged as important modulators of pathogenic mechanisms in PD 71,72 . Transcription factor changes are also of particular interest, as they indicate that there is not only misexpression at the mRNA translation level by miRNA deregulation, but that there exists a second wave of en masse deregulation involving transcription‐wide changes.…”
Section: Discussionmentioning
confidence: 99%
“…“Cellular protein modification,” “Nucleic acid binding transcription factor activity,” “Cell death,” “Catabolic process,” were overrepresented among the biological processes affected. Cellular protein modifications such as phosphorylation, ubiquitination, truncation, acetylation, nitration, and sumoylation of PD‐linked proteins have emerged as important modulators of pathogenic mechanisms in PD 71,72 . Transcription factor changes are also of particular interest, as they indicate that there is not only misexpression at the mRNA translation level by miRNA deregulation, but that there exists a second wave of en masse deregulation involving transcription‐wide changes.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that SUMOylation is part of an endogenous neuroprotective response in ischemic conditions [8][9][10][11][12]. Furthermore, several proteins implicated in ischemia [13], and neurodegenerative disorders [14], such as Alzheimer's [15][16][17] and Parkinson's diseases [18,19], are SUMO targets, and SUMOylation has been linked to agerelated processes [20,21]. As a result, SUMOylation may represent an attractive therapeutic target in several disorders.…”
Section: Introductionmentioning
confidence: 99%
“…'Cellular protein modi cation', 'Nucleic acid binding transcription factor activity', 'Cell death', 'Catabolic process', were overrepresented among the biological processes affected. Cellular protein modi cations such as phosphorylation, ubiquitination, truncation, acetylation, nitration and sumoylation of PD-linked proteins have emerged as important modulators of pathogenic mechanisms in PD [61,62]. Transcription factor changes are also of particular interest, as they indicate that there is not only misexpression at the mRNA translation level by miRNA deregulation, but that there exists a second wave of en masse deregulation involving transcription-wide changes.…”
Section: Discussionmentioning
confidence: 99%